Performance Evaluation of 3D Equipment Model for Laboratory Fume Hoods - Mustafah, Muhammad Syazwan; Yunos, Muhamad Zaini (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Chemical exposure is a significant concern in occupational health, especially for personnel working in chemical laboratories. Laboratory workers have potential exposures to numerous hazardous substances, which can threaten their health. The effects of chemical exposure can vary based on variables such as the type of chemical, its concentration, the duration and frequency of exposure, and the susceptibility of the individual. Current laboratory fume hoods encounter significant challenges due to their heavy reliance on outdated methods, such as simplified models and empirical data, to predict performance. This reliance results in substantial drawbacks that compromise the effectiveness and efficiency of these crucial safety devices and to propose and validate numerical simulation which can predict flow of fume hoods 3D ventilation equipment model and mesh using ANSYS 2023 R1. 3D model and mesh being setup and validation of data using tracer gas test, flow visualization and face velocity measured. For flow visualization, the constricted opening directs the airflow directly onto the front source, potentially increasing its capture efficiency compared to a completely open sash. The fume hood is deemed to be functioning satisfactorily if the detected concentration of the tracer gas outside the hood is lower than the permissible threshold which is below 0.2 mg/m3. Also, Operating the system at half opening increases the air velocity, which improves the likelihood of meeting the required face velocity. Finally, the models confirmed the results obtained from tracer gas and smoke tests and enabled detailed examination of complex airflow dynamics that are difficult to observe physically